(untitled) (Journal of the College of Basic Education, 2023)
Tourism represents for peoples in general a positive phenomenon that they are proud of and is characterized by what it bears of that characteristic, especially religious tourism because of its importance to these peoples and the legacy and belief they bear, representing their beliefs and their religious intellectual orientations. Attracting the population and a positive state in civil peace of peoples’ coexistence despite their different religious and ideological orientations. And in Iraq specifically, and through all the indicators that indicate that Iraq was, is and will become one of the most important centers for attracting religious tourism in the world, as it embraces prominent Islamic and non-Islamic civilizational landmarks that people from different places and countries visit for the purpose of religious tourism, which can play a prominent and effective role. In developing the economic and social aspects, which reflects on providing an acceptable standard of living for the population and thus contributes to the stability and progress of the economic situation of the country. And based on what we mentioned above, the research was divided into four axes. The first axis represents religious tourism in Iraq in the pre-Islamic era among us. The second axis is religious tourism in the era of Islam. In the third axis, I touched on the legal basis for religious tourism in Iraq. As for the fourth axis, the philosophical basis for tourism came. Religious in Iraq.